BUSINESS ETHICS AS ETHICS OF VIRTUE - Razin, A.V. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Filosofii͡a, 2017)
The article shows that the approach associated with the ethics of the virtues, implies the consideration of the qualities that make the activity of a subject possible, speaks of the perfection of an in-dividual from the standpoint of his or her teleological structure, that is speaks about the perfection of a man from the point of view of his destination, perfection in the execution of public functions, unity of goods of the society and the individual. Prospects of application of this approach has been significantly limited as a result of the influence of the Christian tradition in which the actual moral qualities and other abilities of the personality-related skills and dispositions to commit various kinds of social activities were largely separated. At the same time in ancient ethics, in the philosophy of D. Hume, J.S. Mill such a strong separation was not carried out. For applied ethics it is such a broad understanding of virtue has the principle meaning.